The Meaning of Tanka in Novel Garden of Words - Aditya Waskito Jati; Ely Triasih Rahayu; Hartati Hartati (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2020)
This research titled “Denotative, connotative and Myth meaning on tanka in Garden of Words novel by Makoto Shinkai (Roland Barthes Semiotic Approach)”. This research aims to interpret denotative, connotative and myth meaning of tanka through semiotic theory by Roland Barthes. The data used in this research are presented in form of tanka and tanka’s paraphrase that found in this novel. Descriptive Qualitative method is preferred as the main method to analyze meanings of the tanka. Technique of data collection in this research is through literature study.